Formulation and Evaluation of Sublingual Film Loaded with Granisetron Hydrochloride - Sukumaran, Sathesh Kumar (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Sublingual films are well known for its rapid onset of action with enhanced patient agreement. The section of drug absorbed through the sublingual blood vessels by-passes the first-pass metabolism and the bioavailability of the loaded is improved considerably. Difficulty in swallowing, inaccessibility for water to swallow the conventional oral solid dosage forms and unexpected motion sickness are some of the situations that demand the development of sublingual films of Granisetron Hydrochloride. Objectives: To design and develop fast dissolving sublingual films of Granisetron Hydrochloride, with the prime objective to release the drug quickly from the film to facilitate oral absorption. Methods: The sublingual films of Granisetron Hydrochloride was prepared by solvent casting method and evaluated for weight variation and thickness of the film, folding survival test, visual appearance, disintegration time and in vitro dissolution. Results: A gradual increase in weight of the film was observed with increase in the concentration of the polymer. The observed disintegration time of the films was in the range of 13.40–13.64 Seconds. Folding endurance was found to be within the range of 71–77 which indicates that film has good flexibility. The formulation (B3) released about 86.42±0.23% of the Granisetorn hydrochloride within 105 seconds. Conclusion: The newly developed fast dissolving sublingual films of Granisetron Hydrochloride had exhibited faster release of the drug in the in vitro conditions with reliable strength and endurance.